The effect of melatonin on the exosome release and content in in vitro amyloid-beta toxicity model - Ozansoy, Mehmet; Ozansoy, Muzaffer Beyza Çetin; Şahin, Fikrettin; Kılıç, Ülkan (Wiley-Blackwell, 2016)
[Abstract Not Available]
Keywords: Melatonin; Toxicity Model; Exosome